My own words - Ginsburg, Ruth Bader, 1933-2020; Hartnett, Mary Eileen, 1959-; Williams, Wendy (Writer on law) (New York : Simon & Schuster, 2016)
"The first book from Ruth Bader Ginsburg since becoming a Supreme Court Justice in 1993--a witty, engaging, serious, and playful collection of writings and speeches from the woman who has had a powerful and enduring influence on law, women's rights, and popular culture. My Own Words is a selection of writings and speeches by Justice Ginsburg on wide-ranging topics, including gender equality, the workways of the Supreme Court, on being Jewish, on law and lawyers in opera, and on the value of looking beyond US shores when interpreting the US Constitution. Throughout her life Justice Ginsburg has been (and continues to be) a prolific writer and public speaker. This book contains a sampling, selected by Justice Ginsburg and her authorized biographers Mary Hartnett and Wendy W. Williams. Justice Ginsburg has written an Introduction to the book, and Hartnett and Williams introduce each chapter, giving biographical context and quotes gleaned from hundreds of interviews they have conducted. This is a fascinating glimpse into the life of one of America's most influential women"--
Early years and lighter side -- Tributes to waypavers and pathmarkers -- On gender equality: women and the law -- A judge becomes a Justice -- The Justice on judging and justice.
Includes bibliographical references and index.
Donated By Akbar Ali Khan
Keywords: Ginsburg, Ruth Bader, -- 1933-2020.; United States. -- Supreme Court. -- Biography; Women judges -- United States -- Biography; Women lawyers -- United States -- Biography; BIOGRAPHY & AUTOBIOGRAPHY / Lawyers & Judges; BIOGRAPHY & AUTOBIOGRAPHY / Women; POLITICAL SCIENCE / Government / Judicial Branch